Direito à saúde e a judicialização entre pessoas com doenças raras em João Pessoa/PB - Silva, Jadson Kleber Lustosa Ribeiro da (2022)
This thesis addresses the judicialization of health, from a sociological approach, based on an empirical field of judicialization practices of families and people with rare diseases, specifically judicial processes, and interviews with family members and law professionals in the municipality of João Pessoa (Paraíba, Brazil). Thus, this research involves the problematization of the right to health, citizenship, and the role of justice in ensuring medicines and procedures necessary for these people. It is worth noting that João Pessoa, the capital of Paraíba, concentrates a significant part of the demands for health judicialization in the State, which stands out nationally in the number of judicialized cases of certain types of rare diseases. In the same way, people living with rare diseases sue for medicines – of high cost – and gene therapies that guarantee their life quality and survival. Given the need to analyze such issues, this study aimed to understand the phenomenon of health judicialization among people with rare diseases in the municipality of João Pessoa, discussing how different actors influence the achievement of the right to health for people with rare diseases and how the struggle for access to health implies the constitution of biological citizenship. In methodological terms, this is a qualitative study, based on the analysis of 17 lawsuits of people with rare diseases in João Pessoa, in addition to interviews with two mothers of people with rare diseases and two public defenders in the state of Paraíba, as well as a lawyer for the association of people with rare diseases. From the results, we evidenced the importance of the mediation of public defenders in recognizing the right to health for the people and the moral legitimation of suffering by law professionals as a requirement of judicial decisions, based on humanitarian reason. Furthermore, we identified that the judicialization of health expresses the existence of a multifaceted State, characterized by “make live” and, on the other hand, by “make die”; the legal bureaucracy of health judicialization makes people with rare diseases wait; and the use of the risk argument as a fundamental element for promoting or denying the right to health. Finally, we observed the constitution of biological citizenships driven by access to health among people with rare diseases and an incipient analysis of the role of associations and pharmaceutical laboratories in legal pluralism.